Studies on Solute-Solvent Interaction of Different Concentrated Solutions of 1-Carboxamido Pyrazolinein 70% Dioxane-Water and Methanol-Water by Viscosity Measurement. - RAGHUWANSHI, P.B.; DESHMUKH, A.Y.; .G. DOSHI., A (Asian Journal of Chemistry, 2010)
Viscosity measurements have been made on a system comprising 1-carboxamido- 3-(2'-hydroxy-5'-chlorophenyl)-5-anisyl-Δ2-pyrazoline in 70% dioxane-water and 70% methanol-water at 30oC. The data have been used to calculate viscosity and β-coefficient. We have also studied the effect of solvent on viscosity. It has been found that viscosity increases with increase in the percentage of dioxane and methanol. Also, viscosity increased due to increase in the concentration of 1-carboxamido-3-(2' -hydroxy-5' -chlorophenyl)- 5-anisyl-Δ2-pyrazoline (ligand solute) in both solvent dioxane and methanol.